The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1111/jfbc.13431
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the biochemical properties and thermal inactivation of polyphenol oxidase from three lily bulb cultivars

Abstract: The biochemical properties and thermal inactivation of polyphenol oxidase (PPO) from three main planted lily cultivars in China, namely, Lilium lancifolium Thunb, Lilium brownie var. viridulum, and Lilium davidii var. unicolor cotton were evaluated. Data indicate that the PPO from three cultivars showed two optimum pH levels of 4.0 and 6.5-7.0 and temperature of 15°C and exhibited the highest affinity toward 4-methylcatechol. However, this enzyme did not exhibit monophenolase activity. Thiourea and L-cysteine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Researchers have also reported that 4-methylcatechol [ 29 ] and catechol [ 30 ] are the most suitable substrates for PPO purified from apples. Moreover, for the PPOs purified from round brinjal ( Solanum melongena ) [ 31 ], royal dates ( Ziziphus jujuba ) [ 32 ], lily bulb ( Lilium spp ) [ 33 ], and peach ( Prunus persica ) [ 34 ]' 4-methylcatechol is the most suitable substrate. Flavanols (mainly EC) and PCs are the most abundant phenolic substances in apples [ 8 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have also reported that 4-methylcatechol [ 29 ] and catechol [ 30 ] are the most suitable substrates for PPO purified from apples. Moreover, for the PPOs purified from round brinjal ( Solanum melongena ) [ 31 ], royal dates ( Ziziphus jujuba ) [ 32 ], lily bulb ( Lilium spp ) [ 33 ], and peach ( Prunus persica ) [ 34 ]' 4-methylcatechol is the most suitable substrate. Flavanols (mainly EC) and PCs are the most abundant phenolic substances in apples [ 8 , 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…The refractive index value was set to 1.46. The average particle size was calculated by using the volume-weighted average diameter D [4,3] value and the area-weighted average diameter D [3,2] value [26].…”
Section: Particle Size Measurementmentioning
confidence: 99%
“…At the same time, the rich taste and color greatly satisfy consumers' dietary needs. Lily is a perennial herbaceous bulbous plant belonging to the family Liliaceae, which is mainly distributed in the central part of Gansu Province, China [2,3]. Lilies can be divided into medicinal lily and edible lily, of which Lanzhou lily is the only sweet lily that can be used as both medicine and food.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the underground bulbs are rich in various bioactive substances, such as total phenols, total flavonoids, polysaccharides, and saponins [2,3], which contribute to the quality and nutritional value. These compounds are known to have antitumor [4,5], anti-oxidation [6,7], hypoglycemic [8], and anti-inflammatory functions [9,10]. The bulb is an important vegetative reproductive organ for triploid L. lancifolium.…”
Section: Introductionmentioning
confidence: 99%